The temporal structure of male freestyle wrestling bouts in 65, 86 and 125 kg categories - Gutiérrez-Santiago, A.; Vázquez-Estévez, C.; Paramés-González, A.; Argibay-González, J. C.; Reguera-López-de-la-Osa, X.; Vila-Fernández, N.; González-Sabajanes, A.; Prieto-Lage, I. (PLOS ONE, 2023)
In freestyle wrestling, how regulatory breaks and micro pauses affect the efforts during combat has been studied very little. The objective of the study was to determine the temporal structure of fights in male freestyle wrestling in the 65, 86 and 125 kg categories. All wrestlers from the categories (n = 115) who competed in the 2019 senior wrestling world championship (Nur-Sultan, Kazakhstan) participated. Using observational methodology, we analyzed all fights (n = 127). We used different statistical techniques: descriptive, normality tests, Kruskall-Wallis, one-way ANOVA and chi-square. The significance level was ?<0.05. The results show that most fights finish in the last minute (73.5% in 65 kg, 74.5% in 86 kg and 80.6% in 125 kg) and the total fight time is consumed (67.3% in 65 kg, 70.2% in 86 kg and 77.4% in 125 kg). Differences in 18 variables were found when comparing the three weights were found in the temporal and sequential parameters of the combat. When we compare these parameters to the different fight minutes, we find that there are differences in 17 variables in 65 kg, 20 variables in 86 kg and 10 variables in 125 kg. The results define a temporal structure of male freestyle wrestling bouts in the three categories, and therefore, it will be possible to prepare adequate trainings for these athletes. We conclude that in the three weight categories, they wrestle longer standing than while on the ground. There are clear differences between the three categories. In the 125 kg category, the temporal and sequential parameters are more stable throughout the different minutes of the fight, and in 65 and 86 kg, there is an instability. In the three weights, the regulatory break modulates the duration of the pauses and the actions performed by the wrestlers in different fight minutes.